Meningkatkan Prestasi Belajar Bahasa Inggris Dengan Menerapkan Metode Pembelajaran Berbasis Penemuan (Discovery) Pada Siswa Kelas XII TPm SMKN 1 Kalitengah - Hakim, Husnul (MADINAH, 2019)
The objectives of this action research are: (a) Want to know the increase in student achievement after the implementation of discovery learning. (b) Want to know the effect of student learning motivation after the application of the discovery learning method. This research uses three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the students of class X TPM SMKN! middle time . The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement has increased from cycle I to cycle III, namely, cycle I (68.18%), cycle II (77.27%), cycle III (86.36%) and also has a positive impact on increasing students' learning motivation from cycle I to cycle III, namely, Cycle 1 interest (50.00%) attention (59.1%) participation (63.6%), Cycle II interest (68.20%) attention (68, 20%) participation (72.20), cycle III, interest (81.8%) Attention (81.8%) Participation (86.4%). The conclusion of this study is that the discovery method can improve student achievement and also has a positive effect on increasing learning motivation of Class X TPM students at SMK Negeri 1 Kalitengah Lamongan in the 2018/2019 academic year and this learning method can be used as an alternative to learning English